The rooster who would not be quiet! - Deedy, Carmen Agra; Yelchin, Eugene (New York : Scholastic Press, 2017)
The mayor of the noisy city of La Paz institutes new laws forbidding all singing, but a brave little rooster decides he must sing, despite the progressively severe punishments he receives for continuing to crow. The silenced populace, invigorated by the rooster's bravery, ousts the tyrannical mayor and returns their city to its free and clamorous state.
School Library Journal, December 2016
Pub Weekly, November 2016
Kirkus Starred, December 2016
K-3
AD550L
M
Keywords: Villages -- Fiction; Noise -- Fiction; Singing -- Fiction; Roosters -- Fiction